Sistem Informasi Monitoring Warehouse Management Sistem Pada PT. Lisaboy - Hidayat, Rachmat; Novitasari, Rika; Verawati, Ellya (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
PT Lisaboy Gaya Cantika is a trading company engaged in the import and distribution of cosmeticpackaging. The background of this research is based on the problems faced by the company in managing stock items using Microsoft Excel, such as limited real -time data access, data delays andinaccuracies, and difficulties in planning and decision-making related to inventory. This researchuses the waterfall model method with the stages of design, development, and evaluation of a website-based warehouse management system program. Primary data is obtained through interviews withrelevant parties in the company to understand the needs and requirements of the desired system. Inaddition, secondary data is also used to gain an understanding of the current inventory man agement system in the company. The design of the website-based Warehouse Management System programwill include features such as real-time access to inventory data, high-accuracy stock management,effective inventory planning, informed inventory-related decision-making, and direct monitoring of item availability. The program will be developed using web technology and relevant databases. Theresults of this research are expected to assist companies in effectively monitoring inventory,improving stock management accuracy, supporting inventory-related decision-making, and improving operational efficiency in the warehouse.